ICTE 2019 : proceedings of the sixth International Conference On Transportation Engineering, September 20-22, 2019, Chengdu, China - Liu, Xiaobo, 1974-; Peng, Qiyuan; Wang, Kelvin C. P. (American Society of Civil Engineers, 2020)
This collection contains 127 peer-reviewed papers on diverse transportation engineering issues. Topics include: transportation planning and socio-economic development; traffic control and information technology; sustainable transportation methods; rail transit and high-speed rail operations; logistics and supply chain management; and transportation equipment performance and organization optimization. This collection will be of interest to transportation researchers and practitioners as well as transportation planners and government officials.